Analisis Kontribusi Pajak Hiburan Bioskop pada Pendapatan Asli Daerah Kota Pekanbaru - Rahmat Fauzi; Annie Mustika Putri; Rudi Syaf Putra (AKUNTANSI 45, 2024)
The purpose of this research is to determine the contribution of Cinema Entertainment Tax revenue to Regional Original Income, the impact of Government Regulation Number 21 of 2020 on cinema business actors, the obstacles and efforts faced by the Pekanbaru City Regional Revenue Agency on Cinema Entertainment Tax revenue. This research method uses qualitative methods. Data collection used interviews and documentation at the Pekanbaru City Regional Revenue Agency. The results of the interviews I have conducted show that the contribution to Cinema Entertainment Tax in 2020 - 2022 is based on justification in the good category. The efforts made by the Pekanbaru City Regional Revenue Agency to increase cinema entertainment tax revenues are firstly intensification, for those who have not registered, we will register them. secondly, for those who have registered, their tax payments will be seen, if they do not match the real conditions, a tab device will be installed. thirdly digitization and elimination of fines.